STRATEGY FOR THE PREVENTION OF WORLD WARS IDEAL POLITICAL MAP OF THE WORLD, FROM 195 TO 21 MEGA-FEDERATIONS - Luca DIACONESCU; Angelica NECȘULEA (Revista Română de Geografie Politică)
Wars have always caused millions and millions of dead, destroyed peoples' wealth and held development back. Geopolitics, alternative history, futurology or nationalist politics tackle this problem by creating regional paintings, but the results are low compared to expectations, the war due to border disorder is still intense. This research aims to develop a conceptual framework, based on five principles: historical, linguistic, religious, cultural and geopolitical, through which to create a theoretical direction, a map of the world close to the ideal IPMW (Ideal Political Map of the World). The concept of megastates, economically and nationally stable, such as: Brazil, the United States, China, Russia, India or the European Union currently existing, can expand worldwide, materializing in 21 countries with large areas and large populations, encouraging globalization, trade, free movement but above all an optimal framework of the balance of power.